2000
DOI: 10.1081/jbc-100102119
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Antiviral Response by Electric Pulses

Abstract: Antiviral activity was detected in porcine leukocytes obtained from animals killed in a slaughterhouse. The activity appeared in the supernatant immediately after the addition of Sendai virus, an intended interferon (IFN) inducer. Electroinduction appears to be responsible for the production of antiviral molecules in both porcine and human leukocytes. The macromolecule conferring the antiviral activity is sensitive to heat and pH 2.0 treatment. The preformed or electroinduced antiviral activity originating fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In our experiments, we also found [14] that medium-strength square-wave impulses of direct ionic current (DC) can result in a short-term direct antiviral resistance to virus infections and in a consequence to alter the membrane properties of the target cells [15]. We therefore decided to study the changes in the expression of membrane-bound surface marker molecules that are on the surface of the immune competent cells in the human blood [16][17][18]. Our experiments were aimed to establish whether such exogenous electric stimulation of human leukocytes could be utilized as an immune enhancer and an antiviral protector ex vivo, preferably coupled to the dialysis process.…”
Section: Introductionmentioning
confidence: 99%
“…In our experiments, we also found [14] that medium-strength square-wave impulses of direct ionic current (DC) can result in a short-term direct antiviral resistance to virus infections and in a consequence to alter the membrane properties of the target cells [15]. We therefore decided to study the changes in the expression of membrane-bound surface marker molecules that are on the surface of the immune competent cells in the human blood [16][17][18]. Our experiments were aimed to establish whether such exogenous electric stimulation of human leukocytes could be utilized as an immune enhancer and an antiviral protector ex vivo, preferably coupled to the dialysis process.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Pretnar and colleagues 6 reported that one or few strong electric impulses could induce interferon (IFN)-like proteins in human leukocytes that are antigenically different from any contemporary IFN molecule. Kovacs and colleagues 7 found that in porcine leukocytes, the addition of Sendai virus and electric impulses produced porcine interferon a-like molecules. It was found [8][9][10] that 50 Hz EMFs caused phytohemagglutinin (PHA) induction of IFN g and interleukin 6 (IL-6).…”
Section: Introductionmentioning
confidence: 99%